Evaluation of efficacy and safety for compound kushen injection combined with intraperitoneal chemotherapy for patients with malignant ascites: A systematic review and meta-analysis - Yu, Hui-Bo; Hu, Jia-Qi; Han, Bao-Jin; Cao, Hui-Juan; Chen, Shun-Tai; Chen, Xin; Xiong, Hong-Tai; Gao, Jin; Du, Yan-Yuan; Zheng, Hong-Gang (Frontiers in Pharmacology, 2023)
Objectives Compound kushen injection (CKI) combined with intraperitoneal chemotherapy (IPC) is widely used for patients with malignant ascites (MA). However, evidence regarding its efficacy and safety remains limited. The purpose of this review is to evaluate the efficacy and safety of CKI combined with IPC in the treatment of MA. Methods Protocol of this review was registered in PROSPERO (CRD42022304259). Randomized controlled trials (RCTs) on the efficacy and safety of intraperitoneal chemotherapy with CKI in the treatment of MA were searched through 10 electronic databases and 2 clinical trials registration platforms from inception to September 3, 2022. Primary outcome was identified as objective response rate (ORR), and secondary outcomes were identified as quality of life (QoL) and adverse drug reactions (ADRs). The Revman5.4 and Stata17 software were used to calculate risk ratio (RR) at 95% confidence intervals (CI) for binary outcomes and mean difference (MD) at 95% CI for continuous outcomes. Certainty of the evidence was assessed according to the GRADE criteria. Results In this review, 17 RCTs with 1200 patients were included. Risk of bias assessment through the Cochrane risk-of-bias tool showed that one studies was rated as high risk, the others were rated as unclear or low risk. Meta-analysis showed that CKI combined with IPC had an advantage in increasing ORR (RR=1.31, 95%CI 1.20 to 1.43, p<0.00001) and QoL (RR=1.50, 95%CI 1.23 to 1.83, p<0.0001) compared to IPC alone. Moreover, the combined treatment group had lower incidence of myelosuppression (RR=0.51, 95%CI 0.40 to 0.64, p<0.00001), liver dysfunction (RR=0.33, 95%CI 0.16 to 0.70, p=0.004), renal dysfunction (RR=0.39, 95%CI 0.17 to 0.89, p=0.02), and fever (RR=0.51, 95%CI 0.35 to 0.75, p=0.0007) than control group. The quality of evidence assessment through GRADE criteria showed that ORR, myelosuppression, fever was rated moderate, renal dysfunction, liver dysfunction was rated low, and QoL, abdominal pain was rated very low. Conclusions The efficacy and safety of CKI combined with IPC was superior to IPC alone in controlling of MA indicating a potential option in treating MA. However, more high-quality RCTs are still warranted to testify this conclusion.